TIME-RESTRICTED NUTRITION AS A NEW STRATEGY FOR THE THERAPY OF OBESITY AND COMORBID CONDITIONS - Ismoilov, Jamshid Abduraimovich; Egamberdiyeva , Yulduz Komiljon kizi; Mahmamuradova , Nargiza Negmatullayevna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
This manuscript reviews the current literature examining time-restricted eating (TRE) as a tool for treating obesity and comorbid conditions. The search for new nutritional strategies for the treatment of obesity, one of which is POM, is due to the poor adherence of patients to hypocaloric diets in the long term, as well as existing data on the important role of desynchronization of food intake with natural circadian rhythms in the development and progression of obesity and cardiometabolic complications. The article describes the basic mechanisms that regulate circadian rhythms of food intake and nutrient absorption, and substantiates the importance of maintaining a physiological diet to maintain metabolic health. The main part of the review is devoted to the consideration of currently available studies on the effectiveness of various strategies of intermittent energy restriction for reducing body weight and correcting metabolic parameters. Potential mechanisms of the effect of SEM on health are discussed, including those mediated by an unintentional reduction in calorie intake and changes in eating behavior, and differences in the effectiveness of early and late SEM. The article contains an in-depth discussion of the potential problems and controversies associated with the introduction of time-restricted feeding into clinical practice, namely the limited and inconsistent clinical trials available, the lack of data on long-term effectiveness and safety, and the social and psychological limitations that hinder the widespread use of RFE.